EFFECTIVE WAYS AND STAGES OF ENVIRONMENTAL EDUCATION IN THE FORMATION OF ECOLOGICAL CULTURE IN YOUTH (Scientific journal of the Fergana State University, 2024)
The article expresses opinions on the need for environmental education and effective ways to form an environmental culture among young people in the conditions of environmental globalization. Conducting environmental education in educational institutions is of particular importance not only for the conservation of nature, but also for the preservation of human health.